PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH INDUSTRI PERBANKAN (STUDI PADA PT. BRI CABANG SELATPANJANG) - Arifatul Fahmi; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
One strategy that can support business success in the banking sector is trying to offer quality services with high service quality which appears in the performance / performance of existing services (Parasuraman Zeithaml, and Berry, 2003).This study aims to measure how service quality and customer loyalty at PT. BRI branch Selatpanjang well as to examine the effect between these two variables. Customers who sampled totaling 98 people. The data used is primary data collection method of data using questionnaires distributed to 98 respondents. Data analysis methods used in this study is a simple linear regression with SPSS version 18.0.These results indicate that the quality of services provided by the bank BRI branch Selatpanjang already quite good and loyalty of customers, based on the overall results obtained BRI branch bank customers loyal or faithful Selatpanjang to use the products or services provided bank. From the results of the five service quality dimensions studied (tangibles, reliability, responsiveness, assurance and empathy) together show significant results on customer loyalty which means the dimensions of service quality real effect on customer loyalty. From all the tests performed can be concluded that the variable quality of service that is used to explain 69.3% of customer loyalty variable The remaining 30.7% is affected or explained by other variables not included in this study.Keywords: quality of service, customer loyalty, PT. BRI branch Selatpanjang